FRW Cosmological Model with Bulk Viscosity and Phantom Dark Energy in f(R) Gravity - Mete, V. G.; Dudhe, P. S. (Journal of Scientific Research, 2025)
In this paper, The Friedmann-Robertson-walker (FRW) cosmological model with bulk viscosity is investigated in the f(R) theory of gravitation. For the Power and Exponential expansion, the field equations are solved. The functional form of the function f(R) such as f(R) =R+αR2 is chosen for investigation. It is found that the bulk viscosity coefficient reacts similarly to the energy density; the model is viable only for K=-1 , which represents an open universe. The Phantom field potential and scalar field are obtained.